2023
DOI: 10.1177/00469580231172870
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Versus Moderate-Intensity Continuous Training for Improving Physical Health in Elderly Women

Abstract: In elderly women, a lack of regular physical exercise may result in faster decreases in general health and functional performance. Although high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) have been effectively applied in young and clinical groups, there is no evidence to support their use in elderly women to achieve health benefits. Thus, the major goal of this study was to investigate how HIIT affected health-related outcomes in elderly women. Twenty-four inactive eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This strategy might be inferior to a long-term (180 minute) moderate intensity exercise program that exhausts glycogen deposits, when studying IL-6 responses to exercise 66 . Such a program was however deemed infeasible for patients to complete thrice weekly, and the HIIT program used in our study has proven equal or superior to moderate continuous exercise for improving aerobic capacity in multiple patient groups and healthy volunteers 10,11,13,15,16,18,[67][68][69][70][71] . Furthermore, using a widely adapted HIIT protocol will increase our possibility to compare our results to other studies.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy might be inferior to a long-term (180 minute) moderate intensity exercise program that exhausts glycogen deposits, when studying IL-6 responses to exercise 66 . Such a program was however deemed infeasible for patients to complete thrice weekly, and the HIIT program used in our study has proven equal or superior to moderate continuous exercise for improving aerobic capacity in multiple patient groups and healthy volunteers 10,11,13,15,16,18,[67][68][69][70][71] . Furthermore, using a widely adapted HIIT protocol will increase our possibility to compare our results to other studies.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Compared to MCT, HIIT has proven particularly effective at increasing VȮ2max and alleviating fatigue in several other populations than SLE-patients, including healthy 13,14 , middle-aged 15 , and elderly women 16,17 , heart failure patients 10,12 , as well as pre-and perioperative cancer patients 11,18 . As of now, no randomised controlled studies have investigated the impact of HIIT on fatigue or VȮ2max in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results of our study should be interpreted with caution, and more studies are warranted for a robust conclusion. (3) Studies in healthy adults have shown that training intensity is a critical parameter for the improvement of muscle strength and functional ability 66 , 67 . However, insufficient data for this parameter were presented in six included studies, so we were not able to explore the dose–response relationship between it and functional ambulation.…”
Section: Limitations and Conclusionmentioning
confidence: 99%